The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1063/1.3676270
|View full text |Cite
|
Sign up to set email alerts
|

Temperature dependence of current conduction in semi-insulating 4H-SiC epitaxial layer

Abstract: We have investigated temperature dependence (94 K–650 K) of current conduction in semi-insulating 4H-SiC epitaxial layer. The epitaxial layer was grown on highly doped n-type (0001) 4H-SiC substrate using chemical vapor deposition with dichlorosilane precursor. The current—voltage (I-V) characteristics exhibited steps at ∼1 V and ∼70 V that were attributed to the filling of deep level centers by injected electrons. Correlation of the I-V characteristics with the results of thermally stimulated current measurem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 15 publications
1
11
1
Order By: Relevance
“…These dislocation densities are much lower than that reported earlier 7 reflecting improved quality of the epitaxial layer used in this study.…”
Section: à2contrasting
confidence: 49%
“…These dislocation densities are much lower than that reported earlier 7 reflecting improved quality of the epitaxial layer used in this study.…”
Section: à2contrasting
confidence: 49%
“…The hysteresis indicates a possible influence of the interface/bulk states and/or interface dipoles on the I-V characteristics. We have observed similar hysteresis in SI 4H SiC epitaxial detectors [8] which was attributed to the difference in the potential distribution at the Ni/SI-SiC and SI SiC/n+SiC interfaces. Further studies are underway to explain the observed hysteresis in the I-V characteristics.…”
Section: Resultssupporting
confidence: 52%
“…maximum temperatures and results of our work [5], [7],[8], where we perfonned TSC studies of n-type and SI 4H-SiC samples using similar conditions. The peak #3 (Tm � 226 K) may be due to D-center, a B-related defect, boron at C-site (Be) or boron at Si site (Bsi) and carbon vacancy V c[9], whereas peak #4 represent intrinsic defects such as IL l center[10],[11].B.…”
mentioning
confidence: 99%
“…Semi-insulating 50 Good SI-M50 n-typen 50 Good n-M50 n-typen 50 Superior n-S50 n-typen 20 Superior n-S20 Figure 2 represents the I-V characteristics for semi-insulating 4H-SiC epitaxial (SI-M50) samples [14]. It can be observed from the graphs that the I-V characteristics are asymmetric with respect to the polarity of the applied bias.…”
Section: Conductivity Thickness (µM) Quality Designationmentioning
confidence: 99%